ANALISIS INTERPERSONAL MEANING PADA TUTURAN TOKOH MARCUS DALAM SHORT FILM "LOOP" - Puteri Cindy Canadia; Muhammad Rayhan Bustam (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The short film â€œLoopâ€ tells the story of two children named Marcus and Renee who have differences in interacting with other people. Marcus is a boy who talks a lot. In Marcus's utterance, there is interpersonal meaning that can have an interaction impact that connects him with Renee who is a person with autism. This study explains how interpersonal meaning and categories of mood as well as speech functions are used in the utterance of Marcus in the short film "Loop". In this research, the method used is descriptive qualitative method. Data collection techniques in this study were carried out by observation and documentation to show the interpersonal meaning and categories of mood as well as speech functions used in the utterance of Marcus' character. The results of this study indicate that there are three categories of mood and speech functions found in Marcus's utterance which he uses to interact with Renee. By analyzing interpersonal meaning in utterance, it can help to recognize that everyone has different ways of interacting with other people.